ONLINE RESOURCES IN THE PROFESSIONAL EDUCATION OF AIR TRAFFIC CONTROLLERS IN THE USA - Skipalska , Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article considers the introduction and significance of online resources in the professional education of air traffic controllers, in particular in the United States. The article examines the US experience in training air traffic specialists, which can have a positive impact on the development of the Ukrainian aviation industry. Today, online resources are extremely important for future air traffic controllers, as they expand the possibilities of traditional training and contribute to the formation of key professional competencies. It is determined that despite its many advantages, online education faces challenges, including difficulties in attracting students and technical limitations.